Effect of frequency of carbohydrate feedings on recovery and subsequent endurance run - Siu, P. M.; Wong, S. H.; Morris, J. G.; Lam, C. W.; Chung, P. K.; Chung, S. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: This study examined the effect of feeding pattern of a high glycemic index (GI) meal during a short-term recovery on subsequent endurance capacity. METHODS: Eight men ran at 70% .VO2max on a level treadmill for 90 min (T1) on two occasions, followed by 4-h recovery (R) and a further exhaustive run at the same speed (T2). During the R, subjects consumed a prescribed meal with a GI of 77 in either a "gorging" (GOR) or "nibbling" (NIB) intake pattern, providing 1.5 g carbohydrate (CHO) per kilogram body mass. In the GOR trial, the foods were consumed in a single bolus, 20 min after the end of T1. In the NIB trial, the same quantity of food was ingested in three equal portions; the first consumed 20 min after the end of T1 and the remainder at hourly intervals thereafter. RESULTS: The run time during T2 was similar between trials (GOR vs NIB: 68.1 +/- 8.2 vs 66.8 +/- 8.7 min, P > 0.05). However, CHO utilization was lower and fat utilization higher during T2 in the GOR trial compared with the NIB trial (GOR vs NIB: CHO: 94.4 +/- 11.4 vs 117.6 +/- 10.6 g, P < 0.05; FAT: 55.9 +/- 8.0 vs 44 +/- 8.6 g, P < 0.01). CONCLUSIONS: These results suggest that serial consumption of a high GI meal during a 4-h recovery increased the reliance on CHO oxidation for energy provision during a subsequent run when compared with a single feeding. However, there was no difference in the duration of the exhaustive run after the recovery between the GOR and NIB trials.